2021
DOI: 10.1111/andr.13028
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of mental health referral letters for staged and revision genital gender‐affirming surgeries: An unsanctioned barrier to care

Abstract: Background:The World Professional Association for Transgender Health (WPATH) recommends referral letters from two mental health providers within one year of gender-affirming genital surgery (gGAS) to ensure patient readiness before primary surgeries. Many U.S. health insurance plans will not authorize second-and third-stage surgeries or revision surgeries without two referral letters. Such requirements are not supported by WPATH guidelines.Objectives: This study investigates insurance requirements for referral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Consequently, if written documentation or a letter is required to recommend gender-affirming medical and surgical treatment (GAMST), TGD people seeking treatments including hormones, and genital, chest, facial and other gender-affirming surgeries require a single written opinion/signature from an HCP competent to independently assess and diagnose (Bouman et al., 2014 ; Yuan et al, 2021 ). Further written opinions/signatures may be requested where there is a specific clinical need.…”
Section: Chapter 5 Assessment Of Adultsmentioning
confidence: 99%
“…Consequently, if written documentation or a letter is required to recommend gender-affirming medical and surgical treatment (GAMST), TGD people seeking treatments including hormones, and genital, chest, facial and other gender-affirming surgeries require a single written opinion/signature from an HCP competent to independently assess and diagnose (Bouman et al., 2014 ; Yuan et al, 2021 ). Further written opinions/signatures may be requested where there is a specific clinical need.…”
Section: Chapter 5 Assessment Of Adultsmentioning
confidence: 99%
“…Ashley (2019) asserts that the practice is dehumanizing, predicated upon the inherent implication that the medical profession does not trust TNB people to make their own medical decisions, suppresses the diversity of TNB people’s experiences, and is an unjustified double standard when compared to other forms of clinical care. In addition to these ethical considerations offered by Ashley (2019), Yuan et al (2021) also investigated how insurance companies’ referral letter requirements affect TNB patients. Their analysis of over 800 cases at a medical center where referral letters were required for transition-related medical care found that the referral letter process delayed treatment and that insurance companies required patients to follow procedures that went above and beyond what the SOC required.…”
Section: Reflexivity Statementmentioning
confidence: 99%
“…With the SOC Version 8 removing the requirement for referral letters for some specific transition-related medical interventions (but not all), one tension we foresee is that it will take time for insurance companies and medical clinics/providers to adjust their practice of requiring letters. One clear example of this is that some insurance companies even today refer to and at times ask providers to speak to clients’ “real life experience” in their gender (a requirement that was eliminated in SOC Version 7 (Yuan et al, 2021). In addition to the time it takes for insurance companies and medical clinics/providers to update their policies and procedures following the release of the newest SOC Version 8, some may intentionally choose to continue the practice of requiring referral letters in order to minimize liability.…”
Section: Reflexivity Statementmentioning
confidence: 99%
“…in the United States for referral letters for gender-affirming genital surgery can negatively impact care. 13 Both medical and surgical treatment options may adversely affect the reproductive potential of TGD people. Rodriguez-Wallberg et al…”
Section: Yuan Et Al Describe How Burdensome Insurance Company Require...mentioning
confidence: 99%
“…Yuan et al. describe how burdensome insurance company requirements in the United States for referral letters for gender‐affirming genital surgery can negatively impact care 13 …”
mentioning
confidence: 99%